Modern Channel of Distribution. Contemporary Standards and Development Strategies - Kowalska, Katarzyna (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2013)
The article concerns competition in retailing as well as the role and significance of modern marketing strategies in the process of competition. Basic strategies of modern trade in Poland: low-prices policy, location of modern trade in shopping centers, private brands developing, concentration of the trade, are discussed in this paper.